Simulation of Fluid Flow and Heat Transfer Process in Heat Exchangers in Petroleum Industries - Rasul, Hardi Abdulla M.; Barzanjy, Mohammed Jawdat; Aljeware, Hazim Abed Mohammed (International Journal of Membrane Science and Technology, 2023)
Heat exchangers are very useful equipment in a wide range of industries, therefore ?the analysis of the internal flow in them is very important. In this study, a heat exchanger is modeled to solve the flow and temperature field. Three ?turbulence models have been tested for first and second order discretization using ?two different mesh densities, and the results are as follows. The effects of different parameters on the internal conditions of the converter have ?been simulated. The temperature changes decrease in proportion to the reduction of ?the heat transfer coefficient in viscous fluids, and the Reynolds number is greater ?than the Parantel number. For the tube with constant wall temperature and shell inlet, the heat transfer ?coefficient, pressure drop values and heat transfer rate are obtained. In another part, it is shown that the stabilization time of the fluid temperature has a ?direct relationship with the heat capacity of the pipes, and that the performance of ?the tubular heat exchanger with spiral walls is better than that of segmental walls. The intermittent temperature input has been investigated. It has been shown that ?the other flux will fluctuate with the same frequency, which it also proved our ? theoretical results.